Development of a visual Adhesion/Invasion Inhibition Assay to assess the functionality of Shigella-specific antibodies - Batani, Giampiero; Vezzani, Giacomo; Lashchuk, Sabrina; Allaoui, Abdelmounaaim; Cardamone, Dario; Raso, Maria Michelina; Boero, Elena; Roscioli, Emanuele; Ridelfi, Matteo; Gasperini, Gianmarco; Pizza, Mariagrazia; Rossi, Omar; et al. (Frontiers in Immunology, 2024)
Shigella is the etiologic agent of a bacillary dysentery known as shigellosis, which causes millions of infections and thousands of deaths worldwide each year due to Shigella's unique lifestyle within intestinal epithelial cells. Cell adhesion/invasion assays have been extensively used not only to identify targets mediating host-pathogen interaction, but also to evaluate the ability of Shigellaspecific antibodies to reduce virulence. However, these assays are time-consuming and laborintensive and fail to assess differences at the single-cell level. Here, we developed a simple, fast and high-content method named visual Adhesion/Invasion Inhibition Assay (vAIA) to measure the ability of anti-Shigella antibodies to inhibit bacterial adhesion to and invasion of epithelial cells by using the confocal microscope Opera Phenix. We showed that vAIA performed well with a pooled human serum from subjects challenged with S. sonnei and that a specific anti-IpaD monoclonal antibody effectively reduced bacterial virulence in a dose-dependent manner. vAIA can therefore inform on the functionality of polyclonal and monoclonal responses thereby supporting the discovery of pathogenicity mechanisms and the development of candidate vaccines and immunotherapies. Lastly, this assay is very versatile and may be easily applied to other Shigella species or serotypes and to different pathogens.